2011
DOI: 10.1002/app.34459
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of imidazole in polymer electrolyte membranes for elevated temperature anhydrous applications

Abstract: Polymer electrolyte composite membranes were cast from the mixture of Nafion V R ionomer and 2-substituted imidazole. The existing flexible hydrocarbon chain on 2-position of imidazole facilitates proton transfer in the membrane at elevated temperature. The formed composite membrane showed an increased glass transition temperature and improved mechanical property compared with plain Nafion V R membrane. At temperature above 100 C, the ionic conductivity of the composite membrane increases with the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Therefore, CS/GO-X achieve higher and Nafion (0.06 mS cm -1 ), respectively [57]. PGO-filled membranes achieve enhanced anhydrous conductivities when compared with the CS control membrane, which are also comparable to those of Nafion and some other membranes in literatures [58,59].…”
Section: Proton Conduction Properties Of Membranes Under Anhydrous Comentioning
confidence: 53%
“…Therefore, CS/GO-X achieve higher and Nafion (0.06 mS cm -1 ), respectively [57]. PGO-filled membranes achieve enhanced anhydrous conductivities when compared with the CS control membrane, which are also comparable to those of Nafion and some other membranes in literatures [58,59].…”
Section: Proton Conduction Properties Of Membranes Under Anhydrous Comentioning
confidence: 53%
“…The enhanced properties of the composite membrane was attributed to dissociation of proton from sulfonic acid groups on sPEEK relative to the basicity of the SiO 2 -Imi which enhanced proton conductivity by intermolecular proton transfer through hydrogen bonding. Li et al [19] impregnated imidazole into Nafion through a hydrocarbon linker and reported a proton conductivity of $10 À3 S cm À1 under anhydrous state. The T g was observed to increase in the composite due to the electrostatic interaction between imidazole moieties and sulfonic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The design of polymers that self‐assemble through multiple intermolecular interactions such as hydrogen bonding, hydrophobic interactions, π–π stacking, metal‐ligand coordination, and host–guest interactions is a growing field in the last years . Additionally, the biomimetic assembly of imidazole bearing polymers has attracted interest due to their potential as catalyst, their use as polymer electrolytes or metal cation adsorbents . Moreover, the combination of polymers with enzymes has been demonstrated to be beneficial to increase the stability of the biomolecules under harsh operational conditions …”
Section: Introductionmentioning
confidence: 99%
“…[11,30,31] Additionally, the biomimetic assembly of imidazole bearing polymers has attracted interest due to their potential as catalyst, their use as polymer electrolytes or metal cation adsorbents. [32][33][34] Moreover, the combination of polymers with enzymes has been demonstrated to be beneficial to increase the stability of the biomolecules under harsh operational conditions. [35][36][37][38] In this work, we seek to develop a novel and easy method for the fabrication of robust and versatile biocatalytically active films deposited on inorganic surfaces.…”
Section: Introductionmentioning
confidence: 99%